Hepatic fine-needle aspiration cytology: The role of rapid on-site evaluation in the assessment of hepatic lesions - Selhi, Pavneet Kaur; Tyagi, Ruchita; Bansal, Priya; Kaur, Harpreet; Sood, Neena (Turkish Journal of Gastroenterology, 2018)
Abstract Background/Aims: Radiologically guided fine-needle aspiration cytology (FNAC) of internal organs is not cost-effective. Rapid on-site evaluation (ROSE) of smears by a cytopathologist can improve the diagnostic yield of FNACs and save time and money by reducing the need for repeat procedure/biopsy. To determine the role of ROSE in the diagnostic outcome of hepatic lesions by comparative analysis of FNAC with and without ROSE by a cytopathologist. Materials and Methods: Hepatic FNACs were retrospectively analyzed over two separate time periods from January 2011 to June 2013 and from January 2015 to July 2016. Smears from 2015-2016 were subjected to ROSE by a cytopathologist after staining with toluidine blue for 1 min to assess adequacy of the material. Final report was given after hematoxylin and eosin, May Grünwald Giemsa, and Papanicolaou staining were performed. Chi-square test (non-parametric) was used to determine if there was a statistically significant increase in the diagnostic yield with ROSE. Results: During 2011-2013, of the 160 radiologically guided FNACs for hepatic lesions, 22 were non-diagnostic, whereas during 2015-2016, of 142 radiologically guided hepatic FNACs, only six were non-diagnostic. With the application of ROSE, there was a statistically significant increase in the diagnostic yield of hepatic FNACs from 86.25% to 95.8% (p=0.015). Conclusion: ROSE performed by a cytopathologist using toluidine blue can increase the diagnostic yield of hepatic FNACs and reduce the cost of healthcare by eliminating the need for a repeat procedure. Cite this article as: Kaur Selhi P, Tyagi R, Bansal P, Kaur H, Sood N. Hepatic fine-needle aspiration cytology: The role of rapid on-site evaluation in the assessment of hepatic lesions. Turk J Gastroenterol 2018; 29: 442-7.